Music as Liturgical Revelation - Love, Cyprian (Irish theological quarterly, 2004)
The author argues that music is the basis for language, awareness of temporality, and art - Heidegger's three essential dimensions of human consciousness. Thus musicality is crucial for the human person's integration with reality. Also, the author tells us, music is linked universally with hope, another primordial human instinct. Hope, then, is the link between music and religious practices. Thus, in the liturgy, music can assume its rightful role as a vehicle of hope, in the light of Revelation.